Local Government – From the „Small State” to the Social Field - Nijander-Dudzińska, Agata; Wojakowski, Dariusz (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2011)
This article comprises a sketch of the most important perspectives on local government. Among other things, it also aims to present the unique nature of government at the mezzo-social level. Here the concepts of political governing are considered as a social relationship and social resource; proposed, too, is the application of the category of the social field in the analysis of local government. Such social fields are characterized by both relations and resources associated with power when viewed from the standpoint of actions and structures. A separate aspect making itself known in the field of political power is its manifestations and influences.
Władza lokalna – od „małego państwa” do pola społecznego
Keywords: local government; local management; social fields; power relations; local community